The rise of development economics - Naqvi, Syed Nawab Haider (1999)
The rise (and rise) of development economics as a discipline in its own right owes mainly to its overwhelming concern for relevance and for issues which directly and indirectly impinge on raising the economic well-being of the people. As a creative response to episodes of development successes and failures, it has focused on structural transformation, on physical and human capital formation, on extreme poverty and famine, and on "human development". In the process of stimulating research in many important areas, e.g., asymmetric information, moral hazard, the principal-agency syndrome, dynamic external economies, increasing returns, multiple equilibria etc., development economics has entered a new cycle of regeneration and strong growth. It has also helped mainstream economics to move beyond the Arrow-Debreu synthesis and be more alive to real-world problems. - Reproduced
Keywords: Economic and social development